The Differences Of Self-Control In Adolescent Male And Female In Preventing Pre-Marriage Sexual Behavior - Mauliani Mauliani; Rini Julistia (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
This study aims to look at the differences in self-control in adolescent boys and girls in preventing premarital sexual behavior. This study uses a quantitative approach to the type of comparative research and uses a cluster sampling technique. The subjects in this study were 240 adolescents, consisting of 120 boys and 120 girls. The data collectionmethod used a self-control scale compiled by the researcher which consisted of 50 items. Data analysis using independent samples t-test. The results of this study indicate that there are differences in self-control of male and female adolescents in preventing premarital sexual behavior. The self-control of boys is low, in this case boys rarelythink about the impact of what they do. While the self-control of female adolescents is high, in this case female adolescents are able to guide and regulate the right way to behave.